Arginase 1 is upregulated at admission in patients with ST‐elevation myocardial infarction. (23rd August 2021) - Tengbom, John; Cederström, Sofia; Verouhis, Dinos; Böhm, Felix; Eriksson, Per; Folkersen, Lasse; Gabrielsen, Anders; Jernberg, Tomas; Lundman, Pia; Persson, Jonas; Saleh, Nawzad; Settergren, Magnus; et al.
Abstract: Background: The mechanisms underlying rupture of a coronary atherosclerotic plaque and development of myocardial ischemia‐reperfusion injury in ST‐elevation myocardial infarction (STEMI) remain unresolved. Increased arginase 1 activity leads to reduced nitric oxide (NO) production and increased formation of reactive oxygen species due to uncoupling of the NO‐producing enzyme endothelial NO synthase (eNOS). This contributes to endothelial dysfunction, plaque instability and increased susceptibility to ischemia‐reperfusion injury in acute myocardial infarction. Objective: The purpose of this study was to test the hypothesis that arginase gene and protein expression are upregulated in patients with STEMI. Methods: Two cohorts of patients with STEMI were included. In the first cohort ( n = 51), expression of arginase and NO‐synthases as well as arginase 1 protein levels were determined and compared to a healthy control group ( n = 45). In a second cohort ( n = 68), plasma arginase 1 levels and infarct size were determined using cardiac magnetic resonance imaging. Results: Expression of the gene encoding arginase 1 was significantly elevated at admission and 24–48 h after STEMI but not 3 months post STEMI, in comparison with the control group. Expression of the genes encoding arginase 2 and endothelial NO synthase ( NOS3 ) were unaltered. Arginase 1 protein levels were elevated at admission, 24 h post STEMI and remained elevated for up to 6 months. No significant correlation between plasma arginase 1 protein levels and infarct size was observed. Conclusion: The markedly increased gene and protein expression of arginase 1 already at admission indicates a role of arginase 1 in the development of STEMI. Abstract :